The Effectiveness of Token Economy Intervention in Improving Attention in Early Childhood with Concentration Problems in a Kindergarten Setting - Rasyid, Nurfajriyanti (Universitas Negeri Makassar, 2025)
Abstract. This study aims to examine the effectiveness of a token economy intervention in improving attention and task completion in early childhood with attention problems. The study employed a single-subject design with an ABA design on a 6–year–old female kindergarten student (AFP) who exhibited inattentive behavior and difficulty completing assigned tasks. Assessment methods included psychological tests (CPM, Stanford-Binet, VMI), behavioral observations, and interviews with teachers and parents. The token economy intervention was implemented for 4 weeks with princess theme stickers as tokens and backup reinforcers. Results showed significant improvement in task completion from an average of 1.25 tasks (out of 3) during baseline to 2.7 tasks during the intervention phase, with reduced frequency of asking for help from 4 -7 times to 0 – 1 times per day. Follow up data indicated maintenance of behavioral improvements. This study demonstates the effectivess of token economy as a behavioral intervention for improving attention and academic performance in early childhood setting Keywords: token economy, attention, early childhood, behavioral intervention, kindergarten.